2020
DOI: 10.1097/md.0000000000023122
|View full text |Cite
|
Sign up to set email alerts
|

Tissue selecting technique mega-window stapler combined with anal canal epithelial preservation operation for the treatment of severe prolapsed hemorrhoids

Abstract: Introduction: Hemorrhoidal disease is one of the most common and frequently occurring benign anorectal disorders, presented with bleeding and prolapsed, and surgery is the main and effective method for severe prolapsed hemorrhoids. Yet, the recurrence rate after procedure for prolapse and hemorrhoids (PPH) is significantly higher. To reduce the recurrence rate and protect the anus function, we try to carry out a randomized, controlled, prospective study to compare the efficacy and recurrence rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Hemorrhoidal illness is one of the most prevalent benign anorectal conditions, characterized by bleeding and prolapse. According to research, the prevalence among adults is very high [ 1 ]. The global prevalence of hemorrhoids is reported to be 4.4%, with a peak incidence between the ages of 45 and 65.…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhoidal illness is one of the most prevalent benign anorectal conditions, characterized by bleeding and prolapse. According to research, the prevalence among adults is very high [ 1 ]. The global prevalence of hemorrhoids is reported to be 4.4%, with a peak incidence between the ages of 45 and 65.…”
Section: Introductionmentioning
confidence: 99%
“…The experience of clinical observation and medical research indicates that surgical resection combined with other therapeutic methods should be given priority for the treatment of grade III–IV mixed prolapsing hemorrhoids, although debate exists as to which of the multitudinous surgical procedures is the most clinically effective ( 23 ). Pata et al ( 24 ) described the two directions of surgical treatments for hemorrhoids in the first 20 years of the 2000s: modified traditional techniques and minimally invasive techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that 7 d after the operation, the degree of perianal edema in Group A was lower than that in Group B, suggesting that TST33 mega stapler hemorrhoid mucosal resection in the treatment of severe prolapsed hemorrhoids for postoperative perianal edema was reduced to some extent, and two surgical methods for the treatment of severe prolapsed hemorrhoids can improve anal function. TST33 mega stapler hemorrhoid mucosal resection reduces the number of anastomotic nails implanted and reduces the anal bulge, thus protecting anal contraction defecation functions[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%